Implementasi Pendekatan Culturally Responsive Teaching pada Materi Nilai-Nilai Pancasila untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V SDN 45 Mataram - Wahyuni, Sri; Amrullah, Amrullah; Maskur, Maskur (Mataram University, 2025)
This study aims to improve the learning outcomes of fifth-grade students at SDN 45 Mataram on the topic Pancasila Values in Everyday Life through the implementation of the Culturally Responsive Teaching (CRT) approach. The research employed a Classroom Action Research (CAR) method using the Kemmis & McTaggart model, conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 29 students. The results of the study show that the CRT approach can enhance students’ understanding and learning outcomes. The average student score increased from 86.7 in Cycle I to 93.1 in Cycle II. This improvement was supported by more contextual learning, the use of culturally-based learning media, and interactive strategies such as discussions and role-playing. Therefore, the Culturally Responsive Teaching approach is effective for use in Pancasila Education, particularly in fostering students’ understanding of values and character development in elementary schools.